POLA ASUH PEGAWAI LAPAS DALAM PEMBINAAN PERILAKU ANAK SESUAI SYARI'AT ISLAM PADA LPKA BANDA ACEH - Bariah, Chairul; Zulkarnain, Riswan; Lasri, Lasri (Universitas Jabal Ghafur, 2023)
Nurturing is the manner in which guardians teach youngsters, in particular as a type of parental obligation to their kids, as well as a cycle to work on kids' improvement regarding social, physical and profound. Besides, nurturing is a way for guardians to manage physical, social, instructive plans, as well as how to discuss well with kids. The motivation behind this review was to break down the nurturing style of jail staff towards encouraged kids in Class II LPKA Banda Aceh as per the appropriate Islamic regulation. The strategy utilized is a spellbinding subjective methodology. The aftereffects of the review show that jail staff at LPKA assume a significant part in the training system with the obligation of overseeing, security and wellbeing of the helped kids to improve and foster the perspectives and information on the helped youngsters so they are more engaged and deliberate to become somebody who is better and more valuable further down the road mingle. Keywords : Correctional Officer; Child Behavior; Islamic Sharia